DIFFERENTIATED LEARNING STRATEGIES TO IMPROVE THE INTERPERSONAL SKILLS OF STUDENTS WITH DISABILITIES IN SCIENCE LEARNING - Amin, Lailla; Suprihatiningrum, Jamil; Sari, Rita; Halim, Abdul Khaidir; Mafakhir, Ahmad Farros (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study aims to analyze the role of differentiated learning in developing the interpersonal skills of students with disabilities through Natural Science (IPA) learning in an inclusive educational environment. Interpersonal skills, such as social participation, communication, collaboration, and self-confidence, are important competencies that support the academic and social success of students with disabilities, but are often not optimally developed in inclusive practices. This study used a Systematic Literature Review (SLR) design with a descriptive qualitative approach. Data were obtained from reputable national and international journal articles published between 2021 and 2025 and analyzed using thematic analysis techniques. The synthesis results indicate that differentiated learning—especially in the aspect of process differentiation—plays a significant role in improving the quality of social interactions of students with disabilities through flexible grouping, collaborative role assignments, and adjustments to learning activities according to students' readiness and learning profiles. Inquiry-based and collaborative IPA learning has proven to be an effective social space for inclusively training students' communication, cooperation, and self-confidence. These findings confirm that differentiated learning functions not only as an academic strategy but also as a social learning mechanism that supports the development of interpersonal skills in students with disabilities. The implications of this research emphasize the importance of deliberate instructional design, teacher competency in differentiation, and the integration of social goals in inclusive science learning. Keywords: differentiated learning, interpersonal skills, students with disabilities, inclusive education, science learning.